Fried frost / Nurul Alia Noor Imran ...[et al.] - Noor Imran, Nurul Alia; Mohd Alim, Nur Aliyah; Omar Baki, Nur Atirah; Mazni, Nur Afifah; Azmi, Nuradriana (2022)
Fried Frost will be introduced in this business plan. This business is commonly associated with the dessert-based food and beverage industry, which sold fried ice cream. Fried Frost is a partnership-based business with five individuals holding important positions such as General Manager, Administration Manager, Marketing Manager, Operational Manager, and Financial Manager. This business capital is RM12,454.00, with each member contributing RM2494.00 for general manager and RM2490.00 for other manager. This establishment sells fried ice cream with a variety of toppings such as chocolate sauce, caramel sauce, strawberry, banana, and powdered sugar. The business, which has the slogan 'Hot Outside and Melt Inside,' is located inside IOI City Mall in Putrajaya. We will use high-quality ice cream, allowing our customers to enjoy the softness and creaminess of the ice cream, followed by the crunchiness of the bread after frying. Fried Frost's target market is more focused on demographic and geographic segmentation. We chose this geographic segmentation because the location that we chose is strategic and close to residential areas such as Putrajaya, Serdang, and Bandar Baru Bangi for our business. After all, this mall has become an attraction for people in the surrounding area. For demographic segmentation, we targeted persons aged 5-58 years old, people with middle and high income, and our fried ice cream is suited for Malaysians of all races and religions. There are so many competitors that everyone is aware of their presence. Fried Frost uses competition as motivation to focus on everyone's desires. There are a few competitors in the form of Inside Scoop, Rollney, and Street Churos. All three of our competitors are located in the same mall as we are. The menu and the flavor we deliver to our customers distinguish our business from its competitors. Our signature product would be appetizers desserts since we are pushing something that might be a wonderful menu, simpler, and bring people delight. Based on our business plan, we determined that the business we would operate will be profitable even if we sell fried ice cream. We will also make our brand a popular choice in the market. This is due to the fact that the partnership members support each other in working on the establishment of this business